2002
DOI: 10.1046/j.1471-4159.2002.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of NADPH oxidase, neuronal nitric oxide synthase and poly(ADP ribose) polymerase in oxidative neuronal death induced in cortical cultures by brain‐derived neurotrophic factor and neurotrophin‐4/5

Abstract: Certain neurotrophins promote or induce oxidative neuronal death in cortical cultures. However, the effector mechanisms mediating this phenomenon have not been delineated. In this study, we investigated the possibility that NADPH oxidase and nitric oxide synthase (NOS) function as such effectors. Western blot analysis showed that treatment with brainderived neurotrophic factor (BDNF) and neurotrophin (NT)-4/5 increased the levels of NADPH oxidase subunits. Moreover, neurotrophin treatment resulted in membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 44 publications
(86 reference statements)
4
46
1
Order By: Relevance
“…Gao et al (2002) reported a decrease in superoxide levels in rotenone-treated neutrophils preloaded with 5 uM DPI or 0.5 mM APO. Similarly, Hwang et al (2002) reported attenuation in brain-derived neurotrophic factor-induced ROS generation in cortical cultures by 50 uM AEBSF. Although NADPH oxidase inhibitors are relatively nonspecific, the use of 3 different inhibitors with differing mechanisms of action and at concentrations consistent with their selective action on NADPH oxidase support a contribution of the extracellular oxidase in MZ-induced ROS generation.…”
Section: Discussionmentioning
confidence: 85%
“…Gao et al (2002) reported a decrease in superoxide levels in rotenone-treated neutrophils preloaded with 5 uM DPI or 0.5 mM APO. Similarly, Hwang et al (2002) reported attenuation in brain-derived neurotrophic factor-induced ROS generation in cortical cultures by 50 uM AEBSF. Although NADPH oxidase inhibitors are relatively nonspecific, the use of 3 different inhibitors with differing mechanisms of action and at concentrations consistent with their selective action on NADPH oxidase support a contribution of the extracellular oxidase in MZ-induced ROS generation.…”
Section: Discussionmentioning
confidence: 85%
“…at 10 min before MCA occlusion and 10 min before reperfusion markedly inhibited the formation of poly-(ADP-ribose) polymer in cerebral cortex 1 h after reperfusion (D). death without direct inhibition of PARP (Hwang et al, 2002). The DNA alkylating agent-induced NAD depletion is the cause of glycolytic failure and cell death after PARP activation, thus, the maintenance of NAD can mitigate cell death (Ying et al, 2003), suggesting that NAD depletion plays an essential role in the PARP-induced cell death pathway.…”
Section: Discussionmentioning
confidence: 99%
“…5 Rapid DNA single-stranded breaks are induced by ROS, leading to overactivation of PARP and depletion of cellular energy resulting in mitochondrial free radical generation and cell necrosis. 41,42 In our model, PARP inhibition will also block this process and therefore attenuate cell necrosis (Figure 11). In a third step, severe episodes of acute pancreatitis are associated with a systemic inflammatory response.…”
Section: Poly(adp-ribose) Polymerase Inhibition In Acute Pancreatitismentioning
confidence: 96%